2021
DOI: 10.3390/s21165259
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Snowpack Classification Based on Physical Properties Using Near-Infrared Proximal Hyperspectral Data

Abstract: This paper proposes an innovative method for classifying the physical properties of the seasonal snowpack using near-infrared (NIR) hyperspectral imagery to discriminate the optical classes of snow at different degrees of metamorphosis. This imaging system leads to fast and non-invasive assessment of snow properties. Indeed, the spectral similarity of two samples indicates the similarity of their chemical composition and physical characteristics. This can be used to distinguish, without a priori recognition, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Recently, it has been demonstrated that three optical classes of snow with different degrees of metamorphosis (weakly to moderately metamorphosed (WMM), moderately to highly metamorphosed (MHM), and highly to very highly metamorphosed (HVM)) can be identified and discriminated against without prior recognition, based only on NIR hyperspectral data [39]. This study showed that the spectra of snow density are similar within the same optical class and significantly different from one optical class to another.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Recently, it has been demonstrated that three optical classes of snow with different degrees of metamorphosis (weakly to moderately metamorphosed (WMM), moderately to highly metamorphosed (MHM), and highly to very highly metamorphosed (HVM)) can be identified and discriminated against without prior recognition, based only on NIR hyperspectral data [39]. This study showed that the spectra of snow density are similar within the same optical class and significantly different from one optical class to another.…”
Section: Introductionmentioning
confidence: 92%
“…This ensures the recovery of both surface snow and snow from deeper layers (Figure 4a). Once the snow is extracted (Figure 4b), it is scanned with the NIR hyperspectral camera (Figure 5a), and the generated image is analyzed by the Spectronon Pro software (Figure 5b) [39]. The latter identifies the homogeneous layers previously measured in the field and analyzes the spectral responses of each one.…”
Section: In-situ Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations